Penerapan Senam Yoga Terhadap Tekanan Darah Pada Penderita Hipertensi Di Kelurahan Jebres Surakarta - Endyta Youlastri Ayuningtyas; Maryatun Maryatun (Jurnal Anestesi, 2023)
Hypertension is one of the issues challenging the medical community today. In Indonesia, the prevalence of hypertension is 34.1%, or 63,309,630 million individuals. Since hypertension is frequently referred to as the "silent killer," it needs to be treated right once in order to prevent problems like heart failure, stroke, and kidney failure as well as other disorders caused by hypertension. One of the treatments for hypertension is complementary therapy such as yoga therapy. Objective: This research aims to determine the changes in blood pressure as a result of the implementation of yoga exercises in hypertensive patients in Jebres Village, Surakarta City. Methods: This research used a descriptive case study method by observing 2 female respondents aged 45-55 years who were given the implementation of yoga exercises for 4 meetings in 2 weeks with a time of ± 15-20 minutes. Results: Blood pressure dropped following the application of yoga exercises, and grade 1 patients were included. Conclusion: The application of yoga exercises can reduce blood pressure in patients with hypertension.